Dadas as expressões algébricas A,B,C
A=Y^2-3Y
B=2Y^2-Y
C=Y^2-2Y
A- A+B
B- A+B+C
C- A.B
D- A.B.C
Obs: . significa vezes (x)
Lezinha25:
Por favor preciso muito de ajuda
Soluções para a tarefa
Respondido por
5
A + B= y^2 -3y + 2y^2 -y= 3y^2-4y
A+B+C= y^2-3y+2y^2-y+y^2-2y= 4y^2-6y
A.B= (y^2-3y).(2y^2-y)= 2y^4-y^3-6y^3+3y^2=
2y^4-7y^3+3y^2
A.B.C= (y^2-3y).(2y^2-y).(y^2-2y)=
(2y^4-y^3-6y^3+3y^2).(y^2-2y)=
2y^6-4y^5-y^5+2y^4-6y^5+12y^4+3y^4-6y^3=
2y^6-11y^5-17y^4-6y^3
A+B+C= y^2-3y+2y^2-y+y^2-2y= 4y^2-6y
A.B= (y^2-3y).(2y^2-y)= 2y^4-y^3-6y^3+3y^2=
2y^4-7y^3+3y^2
A.B.C= (y^2-3y).(2y^2-y).(y^2-2y)=
(2y^4-y^3-6y^3+3y^2).(y^2-2y)=
2y^6-4y^5-y^5+2y^4-6y^5+12y^4+3y^4-6y^3=
2y^6-11y^5-17y^4-6y^3
Perguntas interessantes
Português,
11 meses atrás
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Biologia,
1 ano atrás